IMPROVING STUDENTS’ VOCABULARY THROUGH VIDEO MEDIA AT SMP NEGERI 7 TONDANO - Chrisanto Pontoan; Noldy Pelenkahu; Sarah Kamagi (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study was to find out whether the video media can improve students’ vocabulary at SMP Negeri 7 Tondano. The strategy for this review utilizes pre and posttest (one gathering pre-test pos-test) plan. Based on the results of the finding and discussion chapter, using video media to improve student vocabulary is effective, because the result of the research on T-test which is the T observed 8.013 > T table 2. 390. And the result of average mean in pretest before the treatment is 70.00 and the result of posttest after the treatment is 86.75 have significant differences. From all the results of the research, it can be concluded that there are significant differences between students who are taught using video media and those who only use confessional methods. Encourage teachers to use video as a medium for teaching and learning activity.